Degradable and biocompatible magnesium zinc structures for nanomedicine: magnetically actuated liposome microcarriers with tunable release - Peter, Florian; Kadiri, Vincent Mauricio; Goyal, Rahul; Hurst, José; Schnichels, Sven; Avital, Aviram; Sela, Mor; Mora-Raimundo, Patricia; Schroeder, Avi; Alarcón Correa, Mariana; Fischer, Peer (Advanced functional materials, 2024)
Inorganic therapeutic carriers and implants should not only be biocompatible, but should also degrade under physiological conditions. Ideally, the time of the degradation can be controlled, and ideally the degradation products are fully biocompatible and metabolized by the body. This proves a challenge for carriers used in nanomedicine, including microswimmers and nanorobotic systems destined for targeted delivery, as these generally require inorganic materials to enable coupling to external fields. Taking inspiration from macroscopic orthopedic implants that are made from magnesium (Mg) and zinc (Zn) and that are fully biocompatible and degradable, the growth of complex microstructures is demonstrated, including micropropellers, containing Mg and Zn. By varying the content of Mg, the corrosion time of the microstructures can be tuned from hours to over a month. Incorporation of biocompatible hard-magnetic iron (Fe)-platinum (Pt) permits the controlled motion of the micropropellers. The surface of the MgZn structures can be functionalized with liposomes, rendering the structures microcarriers that allow for a time-dependent release of their cargo as a results of their degradation in aqueous environments. This suggests a powerful platform for targeted drug or gene delivery, that can be integrated with established systems for magnetic actuation and transfection.